2016
DOI: 10.1007/s13300-016-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia Event Rates: A Comparison Between Real-World Data and Randomized Controlled Trial Populations in Insulin-Treated Diabetes

Abstract: IntroductionHypoglycemia is the most common adverse effect of diabetes therapy, particularly insulin treatment. Hypoglycemia is associated with considerable clinical and economic burden, and may be under-reported. The aim of this study was to com pare the frequency of hypoglycemic events reported in real-world settings with those reported in clinical trials.MethodsWe conducted a structured literature review in PubMed to identify hypoglycemic event rates in patients with type 1 diabetes mellitus (T1DM) and insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
133
2
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 57 publications
14
133
2
10
Order By: Relevance
“…This may have led to misclassification and/or overestimation of hypoglycemic events. Fourth, rates of hypoglycemia observed in randomized clinical trials may be lower than those obtained from real world data (35). Although not a formal exclusion criteria in our trial, physicians may have chosen to exclude patients with recurrent hypoglycemic events or hypoglycemia unawareness, thus resulting in lower hypoglycemia rates compared with the "real world" population with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This may have led to misclassification and/or overestimation of hypoglycemic events. Fourth, rates of hypoglycemia observed in randomized clinical trials may be lower than those obtained from real world data (35). Although not a formal exclusion criteria in our trial, physicians may have chosen to exclude patients with recurrent hypoglycemic events or hypoglycemia unawareness, thus resulting in lower hypoglycemia rates compared with the "real world" population with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the MACE rates observed in real-world studies with those reported in a recent comprehensive meta-analysis of 26 clinical trials 15 . According to the CTTC, The importance of considering RWE has been discussed in prior studies 12,[32][33][34] . Although RCTs are considered the "gold standard" for establishing the efficacy of specific interventions, this methodological approach is probably not sufficient for describing the epidemiology and real-world disease burden in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…This is demonstrated by the stringent patient selection criteria (e.g. exclusion of high risk patients) and highly controlled clinical settings typically employed by RCTs, leading to limited generalizability of disease burden to the general population and routine clinical practices 12,[32][33][34] . Elliot et al 12 found that rates of hypoglycemia were consistently higher in real-world studies compared to RCTs in patients with type 1 or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При всех известных ограничениях исследований реальной практики назначений, связанных как с осо-бенностями системы обеспечения лекарственными пре-паратами, так и с различными подходами к практике ведения больных у различных специалистов, такие дан-ные считаются важным дополнением к официальной статистике и позволяют сфокусироваться на нерешенных проблемах медицинской помощи [11,12]. Данные ана-лиза врачебной практики в нашей стране показали высо-кий уровень расходов при СД2 [13].…”
Section: сахарный диабет Diabetes Mellitusunclassified